Novel modality using computational fluid dynamics to estimate renal pelvic pressure and evaluate severity of obstruction in congenital hydronephrosis - Nishimura, Kenichi; Imada, Syuta; Sugihara, Naoya; Fukumoto, Tetsuya; Miura, Noriyoshi; Miyauchi, Yuki; Kikugawa, Tadahiko; Nakamura, Masanori; Saika, Takashi (Frontiers in Urology, 2025)
BackgroundCongenital hydronephrosis involves obstruction of the ureteropelvic junction, which impairs urine passage and elevates renal pelvic pressure. Elevated renal pelvic pressure detrimentally affects renal function. Pyeloplasty is a surgical procedure that aims to prevent deterioration of renal function. The Whitaker test, which is conducted using nephrostomy, is used to measure renal pelvic pressure. However, this method is highly invasive, highlighting the need for alternative testing approaches. Computational fluid dynamics (CFD) provides quantitative predictions of fluid flow phenomena and has recently been applied in medicine.ObjectiveThe aim of this study was to develop an evaluation method using computational fluid dynamics (CFD) to determine pyeloplasty indications.MethodsThe CFD were analyzed using computed-tomography-extracted images. The urine flow in the extracted geometry was simulated by solving the continuity and Navier–Stokes equations.Key findings and limitationsCFD analysis revealed that renal pelvic pressure increases when urine output increases because of ureteropelvic junction obstruction during hydronephrosis. Furthermore, hydronephrosis with a renal pelvic pressure of 0.015–0.086 Pa, within the physiological urine output range of 360–1440 mL/day, was associated with poor renal function. The main limitation of this method is that the intrarenal pressure analyzed using CFD is an estimate and not the actual pressure.Conclusions and clinical implicationsThus, renal-pelvic pressure can be measured through CFD analysis. Furthermore, CFD analysis can be used as a new modality to determine severity of obstruction.